2023
DOI: 10.1021/acsnano.2c09033
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–Antigen Activated Dendritic Cell Membrane-Coated Biomimetic Nanoparticles with Orchestrating Immune Responses Promote Therapeutic Efficacy against Glioma

Abstract: Immunotherapy has had a profound positive effect on certain types of cancer but has not improved the outcomes of glioma because of the blood−brain barrier (BBB) and immunosuppressive tumor microenvironment. In this study, we developed an activated mature dendritic cell membrane (aDCM)-coated nanoplatform, rapamycin (RAPA)loaded poly(lactic-co-glycolic acid) (PLGA), named aDCM@ PLGA/RAPA, which is a simple, efficient, and individualized strategy to cross the BBB and improve the immune microenvironment precisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 50 publications
0
58
0
Order By: Relevance
“…To camouflage PPy@COF-Por, we harvested HCT116 cancer cell membranes from HCT116 cells using reported methods. [30] By mixing PPy@COF-Por with freshly harvested HCT116 cancer cell membranes in an ultrasonic bath (800 W, 40 kHz) for 30 min, mPPy@COF-Por was obtained. To verify the successful encapsulation of PPy@COF-Por by the cell membranes, we labeled the as-prepared mPPy@COF-Por with a cell membrane staining dye (DiO dye).…”
Section: Synthesis and Characterization Of Mppy@cof-por Nanomotormentioning
confidence: 99%
“…To camouflage PPy@COF-Por, we harvested HCT116 cancer cell membranes from HCT116 cells using reported methods. [30] By mixing PPy@COF-Por with freshly harvested HCT116 cancer cell membranes in an ultrasonic bath (800 W, 40 kHz) for 30 min, mPPy@COF-Por was obtained. To verify the successful encapsulation of PPy@COF-Por by the cell membranes, we labeled the as-prepared mPPy@COF-Por with a cell membrane staining dye (DiO dye).…”
Section: Synthesis and Characterization Of Mppy@cof-por Nanomotormentioning
confidence: 99%
“…Polymer nanoparticles can facilitate drug transport across the BBB and are often used to study brain diseases. [134][135][136][137] For the effective treatment of PD, biodegradable polyethylene glycol-B-polytrimethylene carbonate nanoparticles are developed to promote the sustained release of Ginkgolide B for 48 h, and to prevent neuronal cytotoxicity. 57 Some studies have found that CUR-encapsulated PLGA nanoparticles (Cur-PLGA-NPs) can induce adult neurogenesis by activating the classical Wnt/b-catenin pathway, and Cur-PLGA-NPs may treat neurodegenerative diseases, such as Alzheimer's disease (AD), by enhancing the self-repair mechanism of the brain.…”
Section: Therapeutic Applications Of Chm-derived Nanostructuresmentioning
confidence: 99%
“…DCs activation, aDCM@PLGA/RAPA preparation, and its immunotherapy effect with direct or indirect approaches. Reprinted with permission under a Creative Commons license from ref . Copyright (2023) American Chemical Society.…”
Section: Application Of Bnds In Tumor Immunotherapymentioning
confidence: 99%
“…Moreover, long-term antitumor protection of DCMs-coated SiO 2 NPs was demonstrated in the B16 tumor model. Furthermore, Ma et al developed an activation mature DCMs nanoplatforms to package poly­(lactic- co -glycolic acid) (PLGA) loaded with rapamycin (RAPA), which can effectively enhance homologous targeting ability and blood–brain barrier (BBB) permeability (Figure ). The results confirm that immature DCs can be stimulated to the mature state to further activate tumor-infiltrating T cells and NK cells and to induce subsequent immune responses through direct or indirect approaches.…”
Section: Application Of Bnds In Tumor Immunotherapymentioning
confidence: 99%